Isolated Schistosoma mansoni eggs prevent allergic airway inflammation. (16th September 2018) - Obieglo, Katja; Schuijs, Martijn J.; Ozir‐Fazalalikhan, Arifa; Otto, Frank; van Wijck, Yolanda; Boon, Louis; Lambrecht, Bart N.; Taube, Christian; Smits, Hermelijn H.
Summary: Chronic helminth infection with Schistosoma (S.) mansoni protects against allergic airway inflammation (AAI) in mice and is associated with reduced Th2 responses to inhaled allergens in humans, despite the presence of schistosome‐specific Th2 immunity. Schistosome eggs strongly induce type 2 immunity and allow to study the dynamics of Th2 versus regulatory responses in the absence of worms. Treatment with isolated S. mansoni eggs by i.p. injection prior to induction of AAI to ovalbumin (OVA)/alum led to significantly reduced AAI as assessed by less BAL and lung eosinophilia, less cellular influx into lung tissue, less OVA‐specific Th2 cytokines in lungs and lung‐draining mediastinal lymph nodes and less circulating allergen‐specific IgG1 and IgE antibodies. While OVA‐specific Th2 responses were inhibited, treatment induced a strong systemic Th2 response to the eggs. The protective effect of S. mansoni eggs was unaltered in μMT mice lacking mature (B2) B cells and unaffected by Treg cell depletion using anti‐CD25 blocking antibodies during egg treatment and allergic sensitization. Notably, prophylactic egg treatment resulted in a reduced influx of pro‐inflammatory, monocyte‐derived dendritic cells into lung tissue of allergic mice following challenge. Altogether, S. mansoni eggs can protect against the development of AAI, despite strong egg‐specific Th2 responses.